Plant water relations along a rainfall gradient, between the succulent Karoo and Mesic Mountain Fynbos, in the Cedarberg Mountains, near Clanwilliam, South Africa - Miller, Jeffrey (Department of Biological Sciences, 2016)
The similarities in the structure of the sclerophyllus evergreen shrublands of the five disjunct mediterranean-type ecosystems is thought to be the result of convergent evolution. In the Mediterranean, California, and Chile the length of the summer drought and the cold winter temperatures are hypothesized to be the primary selective pressures. In Australia and South Africa low soil nutrients are thought to be important, as they are in defining the structurally similar heathlands found with a range of climatic types. The fynbos vegetation in an area with a mediterranean-type climate was sampled for a period with low xylem pressure potentials and restricted leif conductances to water loss during the summer drought, and the patterns of plant response to desiccation. The presence of patterns of plant water relations in the fynbos similar to those found in other mediterranean-type ecosystems could demonstrate the importance of water as a selective pressure in the fynbos.